Nucleolar dysfunction in Huntington's disease - Lee, Junghee; Hwang, Yu Jin; Ryu, Hyun; Kowall, Neil W.; Ryu, Hoon (ELSEVIER SCIENCE BV, 2014)
Huntington's disease (HD) is a fatal genetic disorder characterized by triad clinical symptoms of chorea, emotional distress, and cognitive decline. Genetic mutation in HD is identified by an expansion of CAG repeats coding for glutamine (Q) in exon 1 of the huntingtin (htt) gene. The exact mechanism on how mutant htt leads to the selective loss of medium spiny neurons (MSNs) in the striatum is still unknown. Recent studies suggest that nucleolar stress and dysfunction are linked to the pathogenesis of HD. Alterations of the nucleolar activity and integrity contribute to deregulation of ribosomal DNA (rDNA) transcription in HD pathogenesis. Furthermore, epigenetic modifications in the nucleolus are associated with neuronal damage in HD. In this review, we discuss about how post-translational modifications of upstream binding factor (UBF) are affected by histone acetyltransferase and histone methyltransferase and involved in the transcriptional regulation of rDNA in HD. The understanding of epigenetic modulation of UBF-dependent rDNA transcription in the nucleolus may lead to the identification of novel pathological markers and new therapeutic targets to treat HD. This article is part of a Special Issue entitled: Role of the Nucleolus in Human Disease. (C) 2013 Elsevier BM. All rights reserved.
Keywords: RIBOSOMAL-RNA GENES; WILD-TYPE HUNTINGTIN; TRANSCRIPTION FACTOR; POLYMERASE-I; HISTONE ACETYLTRANSFERASE; NEUROLOGICAL PHENOTYPE; STRIATAL NEURONS; SPINY NEURONS; MOUSE MODELS; CAG REPEATS